2021
DOI: 10.3390/biom11010091
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and Chemokines in SARS-CoV-2 Infections—Therapeutic Strategies Targeting Cytokine Storm

Abstract: The recently identified severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus, the cause of coronavirus disease (COVID-19) and the associated ongoing pandemic, frequently leads to severe respiratory distress syndrome and pneumonia with fatal consequences. Although several factors of this infection and its consequences are not completely clear, the presence and involvement of specific chemokines is undoubtedly crucial for the development and progression of COVID-19. Cytokine storm and the often-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 117 publications
1
67
0
Order By: Relevance
“…A network of cytokines and chemokines has been implicated in cytokine storm development in several recent studies. Furthermore, an array of chemokines, including CCL2, CCL3, CCL4, CCL7, CXCL1, CXCL3, CXCL8, and CXCL10, have been reported as critical players in the initiation and progression of the cytokine storm [ 44 , 45 , 46 , 47 ]. The analysis of bronchoalveolar lavage fluid (BALF) from severely ill patients with SARS-CoV-2 infection recently indicated that chemokines play a significant role in disease prognosis.…”
Section: Cytokinesand Chemokines Associated With Cytokine Stormmentioning
confidence: 99%
See 1 more Smart Citation
“…A network of cytokines and chemokines has been implicated in cytokine storm development in several recent studies. Furthermore, an array of chemokines, including CCL2, CCL3, CCL4, CCL7, CXCL1, CXCL3, CXCL8, and CXCL10, have been reported as critical players in the initiation and progression of the cytokine storm [ 44 , 45 , 46 , 47 ]. The analysis of bronchoalveolar lavage fluid (BALF) from severely ill patients with SARS-CoV-2 infection recently indicated that chemokines play a significant role in disease prognosis.…”
Section: Cytokinesand Chemokines Associated With Cytokine Stormmentioning
confidence: 99%
“…Furthermore, recent lung autopsy findings have suggested that seriously ill patients with COVID-19 have considerably higher levels of a set of chemokines, including CCL2, CXCL5, and CXCL6, than moderately ill patients [53]. As a result, several studies that corroborate each other strongly proposed that chemokines are crucially implicated in the poor prognosis, which results in a higher fatality rate [44,45,[53][54][55].…”
Section: Cytokinesand Chemokines Associated With Cytokine Stormmentioning
confidence: 99%
“…Immune hyperreactivity or a failure to resolve the inflammatory reaction due to immune dysregulation in the lungs leads in severely ill patients to excessive production of cytokines/chemokines causing a cytokine storm characterized by elevated levels of circulating cytokines, systemic inflammatory symptoms and multiorgan dysfunction [76] , [77] , [78] . Inflammatory cytokines and chemokines that are elevated in the circulation of patients with COVID-19 include interleukin-1β (IL-1 β), IL-6, TNF, IFN-γ, MCP1 (CCL2), MIP1α (CCL3), MIP1β (CCL4), angiopoietin 2, and vascular endothelial growth factor (VEGF) 79 . The cytokine storm is accompanied by aberrant activation of circulating monocytes, increase in neutrophils, and marked decrease in circulating T and B lymphocytes 27 , 78 .…”
Section: Mechanisms Of Endothelial Injury and Thrombosis In The Vasculature Of Peripheral Organsmentioning
confidence: 99%
“…Besides the cytokines, several other small chemical molecules or chemokines such as CCL2 (MCP1), CCL3 (MIP1α), CXCL10 (IP-10) have been reported to be higher in the serum of severely ill patients with COVID-19 [ 73 , 74 , 75 , 76 ]. These chemokines may correlate with the increased level of cytokines as they act as chemoattractants for several immune cells and lead to the cytokine storm via modulating the immune response in severe cases [ 75 , 76 , 77 , 78 , 79 ]. For example, Chi et al detected the production of pro-inflammatory chemokines and cytokines in the serum samples of asymptomatic as well as symptomatic patients [ 80 ].…”
Section: Factors Influencing Inflammatory Cytokine Production By Modulation Of the Immune Systemmentioning
confidence: 99%
“…The early generation of IL-1RA and IL-10 were found to be correlated with the severity of the disease. The level of most cytokines, including IFN-γ and IL-6, was increased in the later phases of the disease, whereas TNF-α and GM-CSF presented no meaningful differences between mild and severe cases [ 76 , 77 , 83 ]. Furthermore, NLRP3 inflammasome releases proinflammatory cytokines (IL-1β, IL-18) and triggers gasdermin D-mediated pyroptotic cell death, as a result of which elevated level of enzyme lactate dehydrogenase (LDH) is observed in the blood of patients with COVID-19 and correlated with disease severity [ 78 , 84 , 85 , 86 ].…”
Section: Factors Influencing Inflammatory Cytokine Production By Modulation Of the Immune Systemmentioning
confidence: 99%